2018
DOI: 10.1001/jamadermatol.2018.2681
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Treatment of Refractory Granuloma Faciale With Intralesional Rituximab

Abstract: IMPORTANCE Granuloma faciale (GF) is a rare, benign inflammatory dermatosis of unknown cause. Some reports have suggested that it could be part of the spectrum of IgG4-related sclerosing diseases. Granuloma faciale is characterized by single or multiple red-brown nodules, most frequently occurring on the face, and it can produce severe disfigurement. Treatment is difficult, and poor outcomes are often seen. Rituximab is a monoclonal antibody against CD-20 approved by the US Food and Drug Administration for tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…Three patients in one uncontrolled prospective trial received IL‐rituximab, a chimeric murine‐human monoclonal antibody directed against CD20, at 5–10 mg monthly, with two (66%) experiencing CR (defined as >75% improvement) and a reduction in peripheral B‐cells, and 1 (33%) experiencing PR. Side effects included injection site pain, and mild leukopenia in 1 patient 13 …”
Section: Resultsmentioning
confidence: 99%
“…Three patients in one uncontrolled prospective trial received IL‐rituximab, a chimeric murine‐human monoclonal antibody directed against CD20, at 5–10 mg monthly, with two (66%) experiencing CR (defined as >75% improvement) and a reduction in peripheral B‐cells, and 1 (33%) experiencing PR. Side effects included injection site pain, and mild leukopenia in 1 patient 13 …”
Section: Resultsmentioning
confidence: 99%
“…Although usually asymptomatic, GF can cause severe pruritus with impact on quality of life as observed in this case. 3 Management remains challenging given its persistent nature and lack of consensus on treatment. Another layer of complexity is added in patients with comorbidities such as in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Other therapies used with limited available evidence of efficacy include dapsone gel, lasers, systemic steroids, antimalarials, clofazimine, adalimumab, and intralesional rituximab. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
“…However, more recent studies have shown good results after four months with topical tacrolimus 0.1% [10]. Meanwhile, other studies have shown good and promising results with intralesional rituximab [11].…”
Section: Discussionmentioning
confidence: 99%